Design and Performance Evaluation of a Variable Speed Banana Stem Chopping Machine - Ishmatu Aulia Rizky Kirana; Achmad Saifullah Yusuf; Ahmad Radhy; Safira Firdaus Mujiyanti (Jurnal Vokasi Sains dan Teknologi, 2026)
The utilization of banana stem waste in the agricultural sector is still far from optimal, despite its potential as an alternative feed source. The main obstacle stems from the cutting process, which is still performed manually, thus requiring significant time and labor. This study aims to design and implement a banana stem cutting machine controlled by rotational speed settings to improve efficiency. Test results show that the machine can operate within a speed range of 2105–2731 RPM, with a linear blade speed reaching 44.06–57.11 m/s. The resulting chopping capacity reaches 347.04 kg/h, indicating that the machine is capable of processing banana stems efficiently. The designed machine has the potential to improve the utilization of agricultural waste more effectively and sustainably. This study contributes by proposing a variable-speed cutting system based on integrated monitoring and by experimentally analyzing the effect of rotational speed on cutting performance parameters.